Effect of the dietary fibre content of lifelong diet on colonic cellular proliferation in the rat. Issue 8 (August 1992) - Edwards, C A; Wilson, R G; Hanlon, L; Eastwood, M A
Abstract : The effect of the fibre content of lifelong (18 months) diets on proximal and distal colonic cellular proliferation and short chain fatty acid (SCFA) content was investigated in 40 rats. Rats were fed a low fibre diet (17 g/kg non-starch polysaccharides NSP) or the stock diet (133 g/kg NSP). The higher fibre fed rats had increased caecal and colonic total contents (p < 0.001) and SCFAs than the low fibre fed rats (caecal SCFAs: higher fibre rats 96.4 (6.8) mumol/g wet weight v low fibre 22.7 (3.0): p < 0.001, colonic SCFAs: higher fibre 52.3 (3.1) mumol/g wet weight v low fibre 6.9 (2.2) mumol/g wet weight: p < 0.001). Cellular proliferation was increased in the proximal colon (bromodeoxyuridine labelling index, higher fibre 9.3 v low fibre 8.4 p < 0.05; flow cytometry, % cells in S phase higher fibre diet 7.9 v low fibre 6.9; p < 0.01) and there was a shift of proliferating cells to a higher region in each crypt. There was no significant difference in the percentage of cells in S phase in the distal colon of rats in both diet groups. The proliferative zone, however, was expanded in the distal colon of the higher fibre diet fed rats. This study indicates that long term higher fibre intake in rats is associated with a modest increase in cellular proliferation in the proximal colon but not the distal colon.